Seasonal home-range size of the white-tailed deer, Odocoileus virginianus thomasi, in a tropical wetland of southeastern Mexico - Fernando M. Contreras-Morenoa; Mircea G. Hidalgo-Mihart; Rafael Reyna-Hurtado; Carlos A. López-González; Alejandro Jesús-de la Cruz (Revista Mexicana de Biodiversidad)
White-tailed deer, Odocoileus virginianus, home range size (HR) is one of the most studied aspects of its biology.  However, in the southern portion of its distribution, information about its HR is scarce, limiting the capacity for management of the species. To understand the effect of sex and seasonality on the HR of white-tailed deer in a tropical area, we radiotracked 11 adult white-tailed deer (7 females and 4 males) from 2016 to 2019 in a tropical wetland of western Campeche, Mexico. We found female HR to vary from 12.67 ha (±3.52) in the early dry season to 21.57 ha (±18.14) during the late dry season, and from 37.31 ha (±16.93) for the late dry season to 90.16 ha (±72.64) during the rainy season in males. We did not find differences of HR among seasons. However, we found seasonal differences when we tested separately the HR for females and males, showing that female HR is similar among seasons, whereas males had smaller HR during the dry seasons than during the rainy season. Our results indicate that water availability and flooding levels could affect the HR and configuration of the white-tailed deer in the study area.